Uji Kepekaan Avibacterium paragallinarum Terhadap Antibiotik yang Berbeda - Elisabet Tangkonda; Charles Rangga Tabu; Agnesia Endang Tri Hastuti Wahyuni (JURNAL KAJIAN VETERINER, 2019)
Avibacterium paragallinarum is the aetiology of Infectious coryza (snot), one of acute upper respiratory tract diseases, which causes financial loss due to the decrease of egg production in layer. This is Gram negative bacteria which have three serotypes, known as serotype A, B, and C. The aim of this research was to know the sensitivity of Avibacterium paragallinarum to different kinds of antibiotics that are commonly used. This research used Avibacterium paragallinarum culture derived from layer which showed the symptoms of snot. Sensitivity test applied erythromycin, enrofloxacin, gentamycin, amoxicillin and clavulanic acid, and sulfamethoxazol. Results found the sensitivity of Avibacterium paragallinarum to combination of amoxicillin and clavulanic acid was 100%, to erythromycin 50% resistant and 50% intermediate, to enrofloxacin 75% resistant and 25% intermediate, to gentamycin 75% sensitive and 25% resistant, and to sulfamethoxazol 100% resistant.